Chronic disease comorbidity and associated factors among cancer patients in eastern Ethiopia - Birhanu, Abdi; Shawel Lemma, Michael; Habtamu, Biruk; Wondwossen Worku, Nahom; Kitessa, Monas; Nigusie, Shambel; Ayana, Galana Mamo; Tenaw, Yehenaw; Sete, Selamawit; Merga, Bedasa Taye; Mussa, Ibsa (Frontiers in Oncology, 2024)
The existence of long-lasting comorbidities makes cancer management and treatment challenging because of their overlapping poor prognosis. However, there is no data that shows the burden of these chronic cases among cancer patients in Ethiopia. Therefore, this study aimed to assess the burden of and associated factors with chronic disease comorbidity among cancer patients in the eastern part of Ethiopia.A cross-sectional study design was conducted among 422 cancer patients admitted to the only cancer treatment center in Eastern Ethiopia. A simple random sampling technique was employed to select the study participants. Data was extracted from cancer patients' medical records using a checklist. The collected data was entered into the Epi-Data statistical software version 3.1 and then exported to STATA version 17 for analysis. Bivariable and multivariable logistic regressions were used for assessing the association between outcomes and independent variables. Finally, the adjusted odds ratio (AOR) was reported at a 95% confidence interval (CI). The statistical significance of the factors was declared at a p-value of less than 0.05.Results: Out of 422 identified eligible medical records, 419 (99.3%) of them remained in the analysis. A total of 230 (54.8%, 95%CI, 50.0%-59.6%) cancer patients presented with one or more chronic diseases. Of these comorbidities, anemia, hypertension, and cardiovascular disease were the leading diseases. Having obesity at admission [AOR= 1.91, CI: 1.10, 3.61] had a significant association with the comorbidities among cancer patients.The overall prevalence of comorbidity among cancer patients was relatively lower than the studies conducted previous. Being obese was significantly associated with the comorbidities. Attention should be given to the burden of chronic comorbidities among cancer patients by researching, formulating policies, and igniting community literacy against comorbidity. Thus, weight reduction intervention and early detection and treatment of the comorbidities could limit further complications, enhance incidence of other comorbidities.